Drugs in Germany and the United States, 1819-1945: the birth of two addictions - Lewy, Jonathan (Wissen über Waren, 2017)
The use of drugs is as old as history. However, it was only fairly recently that, following the rise of modern medicine, the concept of "drug addiction" was born and came to be seen as a clinical and a social disorder. Focusing on the period from 1800 to the end of World War II, this book traces the way drug addiction developed in two very different countries, i.e. Germany and the United States. On the way, it explains why alcohol is legal whereas heroin and cocaine are not; follows the links between America's war on drugs on one hand and its racism on the other; and demonstrates the very different roles played by the medical establishments in the two countries under consideration. For anyone interested in the history of drugs and medicine, as well as their interaction with politics, justice, and the law, this book is a must